Increasing precipitation weakened the negative effects of simulated warming on soil microbial community composition in a semi-arid sandy grassland - Wang, Shaokun; Jiang, Xingchi; Li, Junyao; Zhao, Xueyong; Han, Erniu; Qu, Hao; Ma, Xujun; Lian, Jie (Frontiers in Microbiology, 2023)
Soil microbial diversity, composition, and function are sensitive to global change factors. It has been predicted that the temperature and precipitation will increase in northern China. Although many studies have been carried out to reveal how global change factors affect soil microbial biomass and composition in terrestrial ecosystems, it is still unexplored how soil microbial diversity and composition, especially in microbial functional genes, respond to increasing precipitation and warming in a semiarid grassland of northern China. A field experiment was established to simulate warming and increasing precipitation in a temperate semiarid grassland of the Horqin region. Soil bacterial (16S) and fungal (ITS1) diversity, composition, and functional genes were analyzed after two growing seasons. The result showed that warming exerted negative effects on soil microbial diversity, composition, and predicted functional genes associated with carbon and nitrogen cycles. Increasing precipitation did not change soil microbial diversity, but it weakened the negative effects of simulated warming on soil microbial diversity. Bacterial and fungal diversities respond consistently to the global change scenario in semiarid sandy grassland, but the reasons were different for bacteria and fungi. The co-occurrence of warming and increasing precipitation will alleviate the negative effects of global change on biodiversity loss and ecosystem degradation under a predicted climate change scenario in a semiarid grassland. Our results provide evidence that soil microbial diversity, composition, and function changed under climate change conditions, and it will improve the predictive models of the ecological changes of temperate grassland in future climate change scenarios.